Impact of Vigorous Exercise on Blood Serum Creatinine Concentration Among Students Athletes: Impact of Vigorous Exercise on Blood Serum Creatinine - Ullah, Moheb; Khan, Alamgir; Jamil, Muhammad; Iqbal Butt, Muhammad Zafar; Ullah, Imran; Zubair, Muhammad; Saheem, Salman; Nasir, Hamza (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Creatinine is a chemical compound left over from energy-producing processes in your Healthy kidneys that filter creatinine out of the blood. Creatinine exits your body as a waste product in urine. Objective: To examine the impact of vigorous-intensity exercises on serum creatinine concentration among student athletes. Methods: Participants were categorized as the control group (CG=n-15) and the experimental group (EG=n-15). Eight-week self-made vigorous intensity exercise protocol was applied on EG. 5 ml blood was collected from each subject, and similarly, serum creatinine concentration was assessed through a serum creatinine test in a biochemistry laboratory. The results (pre and post-test) were statistically tested by independent t-test, mean, and paired sample t-test as statistical tools. Results: A statistically significant difference was found in the Creatinine level between the pretest and posttest scores of EG (P < 0.05) after the treatment. No significant difference was observed in Creatinine level in CG's pretest and posttest scores (P > 0.05). Conclusions: The study shows a considerable difference in the pre and post-test of the subjects of CG and EG, and thus it is shown that vigorous exercise has a positive impact on kidney functions, particularly on creatinine